Labour taxation and its effect on employment growth: Latest estimations with focus on the Czech Republic - Lucie Kábelová; Ondřej Bayer (European Financial and Accounting Journal, 2018)
The paper aims to assess effects of the tax wedge on the employment rate in the Czech Republic. To investigate the impact of the tax wedge on the employment growth, we used a one-equation cointegration model based on the Engle-Granger theorem on OECD data. The results are surprising, because of an unexpected positive relationship between endogenous and exogenous variables. The paper itself is divided into five main parts. The first part is an introduction to the topic and a review of the literature, the second part is on data, the third part is on the statistical methodology and the last two parts cover results and the final conclusion.
Keywords: H24; J30; J38; 650; Employment growth; Personal Income Tax; Tax wedge